EDUKASI MENABUNG SEJAK DINI MENGGUNAKAN INFORMASI DIGITAL DALAM UPAYA MENINGKATKAN GENERASI CERDAS FINANCIAL PADA SISWA SMK MA’ARIF NU KOTA BATAM - Martius Martius; Yulia Yulia; Muh Iqbal Yusuf; Leni Mariani; Desti Asfina (PUAN INDONESIA, 2026)
SMK Ma'arif NU Batam City is a vocational secondary education unit with a development orientation based on Islamic values ????and nationalism. Community service activities aim to provide knowledge and to introduce the basic concept of saving based on information and digital technology. Students' understanding so far is only as a basic tool to store money at home using a piggy bank, understanding the concept of saving in a bank and the use of digital-based information is still not widely understood and digital payment tools are unknown. The results of community service activities for SMK MA'ARIF NU Batam City students are able to provide knowledge and can form the foundation of healthy and sustainable financial behavior in students from an early age. Instilling the habit of saving not only functions as a simple economic practice, but also as an instrument for character formation oriented towards planning, self-control, and financial responsibility. Through a structured educational approach, students are invited to understand the time value of money, the importance of allocating funds, and the long-term benefits of consistent saving. This activity is aimed at encouraging children and adolescents, especially students of SMK Ma'arif NU Batam City, to grow into a financially savvy generation, manage financial resources independently, adapt to developments in digital technology in the financial sector, and be able to actively participate in building an inclusive and sustainable economic ecosystem.